Fairness in Winner-Take-All Markets - Björn Bartling; Alexander W. Cappelen; Mathias Ekström; Erik Ø. Sørensen; Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2018)
The paper reports the first experimental study on people's fairness views on extreme income inequalities arising from winner-take-all reward structures. We find that the majority of participants consider extreme income inequality generated in winner-take-all situations as fair, independent of the winning margin. Spectators appear to endorse a “factual merit” fairness argument for no redistribution: the winner deserves all the earnings because these earnings were determined by his or her performance. Our findings shed light on the present political debate on redistribution, by suggesting that people may object less to certain types of extreme income inequality than commonly assumed.
Keywords: C91; D63; 330; winner-take-all reward structures; fairness; income inequality